School Performance and Behaviour Profiles Among Finnish Adolescents, and Their Relations with Temperament Traits: A Person-centred Approach - Svens-Liavåg, Camilla; Korhonen, Johan; Arnolds-Granlund, Sol-Britt (Scandinavian journal of educational research, 2024)
The aim of this study was to examine what kind of school performance and behaviour profiles could be identified among students in the final grade of basic education in the Swedish speaking parts of Finland (N = 1149, grade 9), how these differed in temperament and how temperament could explain profile differences in first language (L1, Swedish) grades, behaviour grades, and results from standardised reading tests. Latent profile analysis revealed three groups of students with distinct L1 performance and behaviour profiles. One profile with good grades in L1 and behaviour, and good test results - one with satisfactory grades in L1, good grades in behaviour, and poor test results - and one with low grades in L1 and behaviour, and relatively good test results. High perseverance and low impulsivity were related to good L1 and behaviour grades. The findings implicate that student's behaviour impact both the assessment of the subject and behaviour.